The Role of Sports Dedication in Determining the Level of Mental Training in National Athletes - Gacar, Atalay; Nacar, Eyyup; Celik, Fatih; Tutar, Omer Faruk (Lahore Medical & Dental Coll, 2021)
The aim of this study is to examine the effects of national athletes' dedication to sports on mental training levels according to gender, age, sports branch, and the year of being a national athlete, as well as to reveal the effect of dedication to sports on mental training. 101 female and 137 male national athletes between the ages of 10 and 30 who actively do sports in 2020 for various branches and achieved degrees in national and international competitions participated voluntarily. The 'Personal Information Form' prepared by the researchers as a data collection tool and the Sports Dedication Scale developed by Guillen and Martinez-Alvarado to measure the participants' dedication to sports were adapted for athletes and adapted in Turkish by Sirganci et al. Mental Training Inventory in Sports developed by Behnke et al and adapted into Turkish by Yarayan and Ilhan was used to measure the mental training usage levels of the athletes. In order to determine the significance of the differences between the two groups, t-test analysis, and ANOVA were applied to determine the significance between more than two groups in the study. According to the research findings obtained, there is a significant difference in the levels of dedication to sports according to the variables of gender and the year of being a national athlete; there was no difference according to age and sports branch variables. A statistically significant difference was found in the mental training levels of the athletes in terms of gender, age, sports branch and year of being a national athlete. Pearson Correlation analysis was used to determine the direction and severity of the relationship between variables. According to the results of the analysis, it was seen that mental training skills increased as the level of dedication to sports increased.
Keywords: Dedication to Sports; Mental Training; Sports; Psychology